Discerning wisdom: the sapiential literature of the Dead Sea scrolls - Goff, Matthew J. (Supplements to Vetus Testamentum, 2007)
Preliminary Material /M.J. Goff -- Introduction /M.J. Goff -- Chapter One. A Wisdom Text With An Apocalyptic Worldview: 4qinstruction (1q26; 4q415-18, 423) /M.J. Goff -- Chapter Two. Eschatological Wisdom: The Book Of Mysteries (1q27; 4q299- 301) /M.J. Goff -- Chapter Three. Gendered Wisdom: 4qwiles Of The Wicked Woman (4q184) /M.J. Goff -- Chapter Four. The Rewards Of Wisdom: 4qsapiential Work (4q185) /M.J. Goff -- Chapter Five. Wisdom For The Yaḥad: 4qwords Of The Maśkîl To All Sons Of Dawn (4q298) /M.J. Goff -- Chapter Six. Wisdom And Halakhah: 4qways Of Righteousness (4q420-21) /M.J. Goff -- Chapter Seven. Practical Wisdom: The Instruction Of 4q424 /M.J. Goff -- Chapter Eight. Wisdom And The Torah: 4qbeatitudes (4q525) /M.J. Goff -- Chapter Nine. Songs Of Wisdom: Wisdom Psalms In The Hebrew Bible And The Dead Sea Scrolls /M.J. Goff -- Chapter Ten. The Minor Wisdom Texts /M.J. Goff -- Conclusion. The Qumran Wisdom Texts And The Sapiential Tradition /M.J. Goff -- Bibliography /M.J. Goff -- Index Of Authors /M.J. Goff -- Index Of Texts /M.J. Goff.